What are the impacts of the common bean production system on production and quality attributes of the grains? - Cipriano Pinto, Carolina; Borges Lemos, Leandro; Baptista do Amaral, Camila; de Araújo Flôres, Jordana; Prates Coelho, Anderson; Checchio Mingotte, Fábio Luiz (Scientia Agraria Paranaensis, 2021)
The choice of a cultivar can significantly affect grain yield and quality of common bean crops in production systems. The objective of this work was to evaluate the effect of common bean cultivars of the carioca commercial group on grain yield and quality in a production system, and assess the correlation between their variables. The experiment was carried out in the Southeast region of Brazil, in the winter-spring crop season. A randomized block design was used, with 13 treatments and four replications per treatment. The treatments were consisted of common bean cultivars (Pérola, BRSMG-Majestoso, BRS-Estilo, BRSMG-Madrepérola, IPR-Campos Gerais, IPR-Tangará, IPR-Andorinha, IPR-139, IAC-Imperador, IAC-Formoso, IAC-Alvorada, IAC-Milênio, and TAA-Bola Cheia). The choice of a cultivar affects production and quality attributes of common bean in production systems, as it can result in increases of up to 34% in grain yield, 20% in grain yield in sieves equal to or higher than 12 (GYS≥12), 16% in grain protein contents, and 47% in cooking time. The cultivar BRSMG-Majestoso presented the highest grain yield (3,805 kg ha-1), and IPR-Andorinha and BRSMG-Madrepérola stood out with GYS≥12 of 93% and grains with clear integument, respectively. Grain yield increases as the number of pods per plant and grains per pod increase, presenting a negative correlation with crude protein contents and cooking time.